Teoria wiskozymetrów dla jednorodnych mieszanin gruntowo-wodnych - W. Parzonka (Engineering Transactions)
This paper contains a theoretical analysis of fundamental viscometric instruments for homogeneous water-soil mixtures. These mixtures are composed of water and soil grains, the size of which is 2 to 50-100u. The rheologic behaviour of such mixtures depends on the properties of the solid particles: their form, size, specific weight and, in particular, their concentration. The limit concentration slim is an important characteristic of the mixture: which has the properties of a Newtonian body for s’lim and those of a non-Newtonian body above this limit. Correct determination of the rheologic properties of a water-soil mixture can be achieved by models of flow of viscoplastic bodies, the rheologic properties of which are independent of time, that is a) The Newtonian model (1) for low concentration mixtures, having the properties of a two-phase liquid, for s' < s’lim; b) The Bingham (2) or De Waele-Ostwald (3) model for high concentrations, s' < s’lim. An important condition of correct measurement is the application of viscometers (viscosimeters) designed for the required accuracy of measurement and the type of liquid to be investigated. For homogeneous water-soil mixtures with large grains viscometers of a relatively wide gap (of the order of 1 mm or more) should be applied. This requirement is satisfied only by rotational visco-meters (viscosimeters) of the Couette type or tube type viscometers. The cone-plate type is not suitable the gap: (which is- below 10-10u) being too small. he paper explains a theory of flow of the three bodies just mentioned through viscometers of both types. The Couette viscometer is much more accurate, because it ensures quasi-homogeneous stress field and a wide range of linear measurement. The paper contains also a description of methods of accurate measurement and viscometers for Bingham-type plastic bodies and pseudo-plastic bodies. It contains also a selection of description, 1) for Bingham bodies, of a) a method of selection of a Couette viscometer knowing the order of magnitude of the number τ0/ηp and the parameters of the viscometer characterized by the number a = R_2^2/R_(1 )^2and the maximum angular Ωmax, b) a method of selection of a tube type viscometer the linear range of which is characterized by the generalized Reynolds number Re*; 2) for pseudo-plastic bodies is proposed a) a method of correction of the measurement results obtained by means of viscometers of the Couette type. It is shown also that the difference between the pseudo-coefficient of rigidity kap and its real value k can be disregarded under the condition that a viscometer In this case the maximum deviation is smaller than 3,8%; of a < 1,10 is used. b) a method of determining the linear measurement range for rotational viscometers and tubes.